PochIoT: Design and Implementation of an IoT-Based System for Tank Barrel Inspection - (:unkn) unknown (Springer Nature Singapore, 2024)
The inspection of confined spaces has been a common area of interest for various studies. However, the inspection of tank barrels and the management of the data obtained using current cloud technologies is a topic that has not been fully explored. Regard...
Keywords: Internet de las cosas; Inspección de tanques